Potential Role of Long Non‐Coding RNA in Osteogenic Differentiation of Human Periodontal Ligament Stem Cells. Issue 7 (1st July 2016) - Qu, Qian; Fang, Fuchun; Wu, Buling; Hu, Yanwei; Chen, Ming; Deng, Zilong; Ma, Dandan; Chen, Ting; Hao, Yilin; Ge, Yihong
Abstract : Background: Long non‐coding RNAs (lncRNAs) are emerging as important regulators of eukaryotic gene expression and have been shown to regulate various modular components of development and differentiation. However, the roles of lncRNAs in the regulation of osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) remain poorly understood. Methods: Expression patterns of lncRNA and messenger RNA (mRNA) during osteogenic differentiation were profiled using microarray analysis. Quantitative reverse transcription polymerase chain reaction was performed to validate the microarray data. Biologic functions of candidates were revealed by: 1) cluster analysis; 2) gene ontology (GO); and 3) pathway analysis. Coding–non‐coding gene coexpression (CNC) networks were constructed to investigate potential regulatory roles of lncRNAs and osteogenesis‐related mRNAs. Results: After osteoinduction, 3, 557 mRNAs and 2, 171 lncRNAs were differentially expressed, of which 994 lncRNAs were upregulated and 1, 177 were downregulated (fold change >2.0 or <−2.0; P <0.05). Cluster analysis showed that lncRNAs and mRNAs from the experimental and control groups belonged to different clusters. GO analysis demonstrated that: 1) cellular process; 2) biologic regulation; and 3) regulation of biologic process were the most significant groups related to induction. Pathway analysis indicated that 83 pathways corresponded to differentially expressed mRNAs, including: 1) mitogen‐activated protein kinase; 2) vascular endothelial growth factor; and 3) transforming growth factor‐β signaling pathways. CNC network analysis indicated that 393 lncRNAs were closely related to osteogenesis‐related mRNAs. Conclusions: Expression profiles of lncRNAs and mRNAs were significantly altered during osteogenic differentiation of hPDLSCs. This result suggests that lncRNAs may play crucial roles in this process and could regulate mRNA expression.